Hydrogeological activity in southern Peru, a situational assessment of the Sama and Locumba basins - Franco, Alberto (2012)
It is known that South America has an intense geothermal activity product of plate movement on the shores of the Pacific Ocean, the geothermal activity in Peru is especially intense in the southern regions especially in Arequipa, Moquegua and Tacna, the latter is one of the main, which accounts for 29 percent of the national activity. His influence can be positive, as might be the possible use as an energy source, but also negative for the high load of pollutants made on these underlying basins, such as basins and Locumba Sama, which are grounds for this report . Furthermore, the very nature through mechanisms such as dilution with water sources good quality iron flocculation or natural origin, contributes significantly to the control of some contaminating metals such as arsenic, for example in the if Sama basin, improves quality by almost fifty percent. In this article, we compare this situation and its possible implications of treatment in the development of the affected zones.